Physicochemical kinetics of rapid soil stabilization using calcium sulfoaluminate-based cements - Nicholas Benjamin Petersen; Ashish Bastola; Pavan Akula; John Rushing (Cement)
Rapid stabilization of weak soil offers a promising option for quick infrastructure development and soil repair. The interaction between the rapid stabilizer and the soil is critical in defining its strength and durability. This study investigates the physicochemical effects of using Calcium Sulfoaluminate (CSA) cement-based stabilizers for rapid stabilization of weak clays, focusing on early age (<1 day) reaction kinetics and its effect on the short-term and long-term engineering characteristics. Geochemical modeling is proposed to model the chemical kinetics and predict the formation of strength-enhancing products in the stabilized soil mixtures. The study investigates the unconfined compression strength and durability (cyclic wetting and drying) of stabilized soil. Results showed stabilizers with a higher proportion (50 wt. percentage or more) of CSA (CSA-rich) achieved up to 80 % of the 28–day strength in 60 min after stabilization. Mineralogical characterization using X-Ray Diffraction, Thermogravimetric Analysis, and Scanning Electron Microscopy, identified Ettringite in CSA-rich stabilizers and Calcium-Silicate-Hydrates (C-S-H) in stabilizers with a higher (50 wt. percentage or more) proportion of Portland Cement (PC-rich) stabilizers as key strength-enhancing products. Integrating the modeling results with the engineering and mineralogical characterization provided valuable insights into the rapid stabilization mechanisms of CSA cement.